Assessment for the Risk Factors of Polypharmacy in Elderly Patients - Mustafa Majed Helayeel; Dhuha Ahmed Majeed; Noor Mohammed Falih; Inam Sameh Arif; Amani Anees Abbody (Indian Journal of Forensic Medicine & Toxicology, 2021)
Polypharmacy is typical clinical issue in elderly people, it includes prescribed medications, over-the-counter (OTC) and herbal preparations.A total of 173 Iraqi elderly patients of age 60 years and above, were enrolled in this study. Data were collected using structured, cross-sectional questionnaire-based survey. List of required data were recorded by interviewing patients during admission to Baghdad teaching hospital, Al-Yarmouk teaching hospital and 3 community pharmacies in Baghdad governorate. From August - September 2019 in Baghdad-Iraq. Data were analyzed using SPSS software (version 25). Relationships between daily drug consumptions (DDC) and other continuous variables were examined using spearmen’s correlation. For between-group comparisons of daily drug consumptions, Student’s t-tests were performed. For categorical variables with more than 2 categories, multi-factor ANOVA (Analysis of variance) was performed.Significant number of the older Iraqi patient population has a high prevalence of polypharmacy with a highprevalence of consumption of lipid modifying drugs, proton pump inhibitor, oral antidiabetic drugs, and angiotensin II receptor antagonist. according to this study. The findings of this study showed that the higherDDC was significantly associated with hypertension alongside higher number of comorbidities, ADRs andPIM. Intraclass polypharmacy was highly associated with anti-hypertensives and lipid modifying drugs, suggesting revision of the drug-dispensing policy among older Iraqi population.